College Algebra (6th Edition)

Published by Pearson
ISBN 10: 0-32178-228-3
ISBN 13: 978-0-32178-228-1

Chapter 4 - Exponential and Logarithmic Functions - Exercise Set 4.4: 102

Answer

Since $x \ne -2$, then $x = 6$

Work Step by Step

$3^{x^{2}-12} = 9^{2x}$ $3^{x^{2}-12} = (3^{2})^{2x}$ $3^{x^{2}-12} = 3^{4x}$ $x^{2} - 12 = 4x$ $x^{2} - 4x - 12 = 0$ $(x-6)(x+2) = 0$ $x = 6, -2$ Since $x \ne -2$, then $x = 6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.